Transgender disclosure decisions and workplace socio-cultural dynamics. (3rd April 2021) - Yasser, Qaiser Rafique; Agrawal, Reena; Ahmed, Irfan
ABSTRACT: The underlined paper aimed at taking transgender individual disclosure decisions in a workplace to be a matter of socio-cultural dynamics. Hence, the place of transgender individuals, defined by the religious and socio-cultural values especially of Muslim society, triggered the very thought of this research. So, Pakistan and Bangladesh, being the Muslim countries, were involved for its data. Thus, the results of the exhaustive interviews with the transgender individuals exhibited the influence of the socio-cultural factors, innately rooted in the environment, on the disclosure decisions in the workplace and non-workplace environments. The respondents believed that the disclosure decision in the workplace, between non-disclosures to the plenary and total disclosure ranges was influenced by the family reputation complexities, a tightly integrated communal network, ethical obligations and the predominant religious views in the society. The current research developed our understanding of gender identity and the disclosure decision of the transgender individuals while elucidating the mechanism in which the socio-cultural factors are the incomprehensible contour of their decision emergence act.